Uncertainty analysis of reactor safety systems with statistically correlated failure data - Dezfuli, H.; Modarres, M. (Reliability engineering, 1985)
The probability of occurrence of the top event of a fault tree is estimated from failure probability of components that constitute the fault tree. Component failure probabilities are subject to statistical uncertainties. In addition, there are cases where the failure data are statistically correlated. Most fault tree evaluations have so far been based on uncorrelated component failure data. The subject of this paper is the description of a method of assessing the probability intervals for the top event failure probability of fault trees when component failure data are statistically correlated. To estimate the mean and variance of the top event, a second-order system moment method is presented through Taylor series expansion, which provides an alternative to the normally used Monte-Carlo method. For cases where component failure probabilities are statistically correlated, the Taylor expansion terms are treated properly. A moment matching technique is used to obtain the probability distribution function (pdf) of the top event through fitting a Johnson S B distribution. The computer program (CORRELATE) was developed to perform the calculations necessary for the implementation of the method developed. The CORRELATE code is very efficient and consumes minimal computer time. This is primarily because it does not employ the time-consuming Monte-Carlo method.